Immune checkpoint inhibitor‐mediated psoriasis treated with biologics - Pei Ming Yeo; Nisha Suyien Chandran (Wiley, 2023)
Abstract Skin toxicities are the most prevalent immune‐related adverse events of immune checkpoint inhibitors (ICIs), but psoriasis is uncommon. To date, there are no treatment guidelines for this unique patient cohort. We describe a case of ICI‐mediated psoriasis and its treatment using a tumour necrosis factor‐α blocker. A 61‐year‐old Chinese female with stage IV intrahepatic cholangiocarcinoma experienced significant worsening of her chronic plaque psoriasis and nail psoriasis 1 week after her second cycle of pembrolizumab. The patient developed extensive thin scaly psoriatic papules and plaques (psoriasis area and severity index (PASI) 9.1, body surface area (BSA) 40%) involving her abdomen, back, arms and legs. Two months before the start of pembrolizumab, she had psoriatic plaques (PASI 0.9, BSA 5%) treated only with topical 0.1% betamethasone valerate cream, urea 10% cream and coal tar 25% shampoo. We initiated adalimumab given the extent of BSA involvement and severity of the flare of chronic plaque psoriasis. Two months later, her psoriasis improved (PASI 9, BSA 19%) and pembrolizumab was continued. Eight months after the initiation of adalimumab, her chronic plaque psoriasis remained stable and her cholangiocarcinoma remained in remission. We hope to share our experience of using biologics to attain prompt control of ICI‐mediated psoriasis.